2013
DOI: 10.1097/fpc.0000000000000000
|View full text |Cite
|
Sign up to set email alerts
|

GABRG2, rs211037 is associated with epilepsy susceptibility, but not with antiepileptic drug resistance and febrile seizures

Abstract: We could substantiate that among the GABA(A) receptor subunit gene cluster polymorphisms, the GABRG2, rs211037 predisposes susceptibility to epilepsy, irrespective of its phenotype, but not to AED resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 26 publications
0
39
0
Order By: Relevance
“…Transporter hypothesis has been the most preferred choice for understanding the drug resistance and often ignoring the likelihood of a multifactorial nature of drug resistance and the complexity of the events regulating transporters and the role of genetic variants in drug targets. In an earlier study on the same population we reported that a synonymous variant in GABRG2 rs211037 and SCN1A rs3812718 may have a putative role in increasing the risk of epilepsy, which was independent of its phenotype, that is, MTLE-HS or Juvenile myoclonic epilepsy [ 23 ], [ 57 ]. Functionally significant association of drug target genes such as GABRG2 and SCN1A and efflux transporter gene ABCB1 to susceptibility to epilepsy in the present population needs to be seen in combination rather than isolation in evaluating therapeutic response.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Transporter hypothesis has been the most preferred choice for understanding the drug resistance and often ignoring the likelihood of a multifactorial nature of drug resistance and the complexity of the events regulating transporters and the role of genetic variants in drug targets. In an earlier study on the same population we reported that a synonymous variant in GABRG2 rs211037 and SCN1A rs3812718 may have a putative role in increasing the risk of epilepsy, which was independent of its phenotype, that is, MTLE-HS or Juvenile myoclonic epilepsy [ 23 ], [ 57 ]. Functionally significant association of drug target genes such as GABRG2 and SCN1A and efflux transporter gene ABCB1 to susceptibility to epilepsy in the present population needs to be seen in combination rather than isolation in evaluating therapeutic response.…”
Section: Discussionmentioning
confidence: 84%
“…These patients had seizures for a mean duration of 18.7 (range 6 to 50) years, and had failed multiple AED trials prior to ATL. All of them had received at least two of the old AEDs (phenobarbital, phenytoin, carbamazepine and valproate), and half of them, in addition, had received at least one of the new AEDs (clobazam, lamotrigine, oxcarbazepine, topiramate and Levetiracetam) [ 23 ]. We have described our protocols for pre-surgical evaluation, selection for ATL and post-ATL follow-up in detail elsewhere [ 24 ], [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review provides an updated perspective on the accumulating evidence on common susceptibility alleles in this IGE subtype. In the 50 association studies reviewed, most polymorphisms were examined in one case–control study, of which just 17% had a positive association[34,43,4749,5153,55,58,61,62,64,6669,71,77,80–83]. However, taking into account the high a priori risk of false positive results in candidate gene association studies[25], a discussion of the biological significance of these cases was precluded.…”
Section: Discussionmentioning
confidence: 99%
“…To date, pathogenic variants in the GABRG2 gene, including 11 truncating variants (four nonsense, four frame-shifts, two splice-sites, and one large deletion) and 16 missense variants, have been reported in a subset of families and individuals with a variety of phenotypes ranging from epileptic encephalopathies (including Dravet syndrome) to genetic (generalized) epilepsy with febrile seizures plus (GEFS+), to febrile seizures associated with childhood absence epilepsy (CAE) and milder simple febrile seizures (FS) (Baulac et al, 2001; Wallace et al, 2001; Harkin et al, 2002; Kananura et al, 2002; Audenaert et al, 2006; Hirose, 2006; Sun et al, 2008; Macdonald et al, 2010; Shi et al, 2010; Cantarín-Extremera et al, 2011; Lachance-Touchette et al, 2011; Balan et al, 2013; Carvill et al, 2013; Tian et al, 2013; Johnston et al, 2014; Boillot et al, 2015; Reinthaler et al, 2015; Shen et al, 2017). In these studies, the majority of pathogenic variants in GABRG2 segregated predominantly with a FS phenotype.…”
Section: Discussionmentioning
confidence: 99%